Idea Formulation for Spoken Language Production: The Interface of Cognition and Language. (15th November 2019) - Barker, Megan S.; Nelson, Nicole L.; Robinson, Gail A.
Abstract: Background: Language and communication are fundamental to the human experience, and, traditionally, spoken language is studied as an isolated skill. However, before propositional language (i.e., spontaneous, voluntary, novel speech) can be produced, propositional content or 'ideas' must be formulated. Objective: This review highlights the role of broader cognitive processes, particularly 'executive attention', in the formulation of propositional content (i.e., 'ideas') for propositional language production. Conclusions: Several key lines of evidence converge to suggest that the formulation of ideas for propositional language production draws on executive attentional processes. Larger-scale clinical research has demonstrated a link between attentional processes and language, while detailed case studies of neurological patients have elucidated specific idea formulation mechanisms relating to the generation, selection and sequencing of ideas for expression. Furthermore, executive attentional processes have been implicated in the generation of ideas for propositional language production. Finally, neuroimaging studies suggest that a widely distributed network of brain regions, including parts of the prefrontal and parietal cortices, supports propositional language production. Implications: Theoretically driven experimental research studies investigating mechanisms involved in the formulation of ideas are lacking. We suggest that novel experimental approaches are needed to define the contribution of executive attentional processes to idea formulation, from which comprehensive models of spoken language production can be developed. Clinically, propositional language impairments should be considered in the context of broader executive attentional deficits.